Thermally Activated Delayed Fluorescence in Polymers: A New Route toward Highly Efficient Solution Processable OLEDs. (12th October 2015) - Nikolaenko, Andrey E.; Cass, Michael; Bourcet, Florence; Mohamad, David; Roberts, Matthew
Abstract : Efficient intermonomer thermally activated delayed fluorescence is demonstrated for the first time, opening a new route to achieving high‐efficiency solution processable polymer light‐emitting device materials. External quantum efficiency (EQE) of up to 10% is achieved in a simple fully solution‐processed device structure, and routes for further EQE improvement identified.